2018
DOI: 10.1094/mpmi-02-18-0048-r
|View full text |Cite
|
Sign up to set email alerts
|

Tomato 14-3-3 Proteins Are Required for Xv3 Disease Resistance and Interact with a Subset of Xanthomonas euvesicatoria Effectors

Abstract: The 14-3-3 phospho-binding proteins with scaffolding activity play central roles in the regulation of enzymes and signaling complexes in eukaryotes. In plants, 14-3-3 isoforms are required for disease resistance and key targets of pathogen effectors. Here, we examined the requirement of the tomato (Solanum lycopersicum) 14-3-3 isoform (TFT) protein family for Xv3 disease resistance in response to the bacterial pathogen Xanthomonas euvesicatoria. In addition, we determined whether TFT proteins interact with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…To determine the biological significance of Me10's interaction with TFT7, we first examined if aphid feeding regulates TFT7 expression. Earlier studies showed that TFT7 is a positive regulator of tomato defense signaling (Oh et al ., ) and that its mRNA abundance increases upon pathogen infection (Dubrow et al ., ). We evaluated the temporal expression pattern of TFT7 mRNA in leaves of susceptible tomato plants at multiple time points after potato aphid infestation using reverse transcription real‐time qPCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the biological significance of Me10's interaction with TFT7, we first examined if aphid feeding regulates TFT7 expression. Earlier studies showed that TFT7 is a positive regulator of tomato defense signaling (Oh et al ., ) and that its mRNA abundance increases upon pathogen infection (Dubrow et al ., ). We evaluated the temporal expression pattern of TFT7 mRNA in leaves of susceptible tomato plants at multiple time points after potato aphid infestation using reverse transcription real‐time qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that binding of these aphid effectors to TFT7 may be isoform specific. Isoform‐specific interactions have been previously reported for members of 14‐3‐3 proteins with their clients (Bridges & Moorhead, ), as well with pathogen effector proteins (Kim et al ., ; Teper et al ., ; Dubrow et al ., ). BiFC microscopy studies with Me10 and TFT7 suggest that formation of an Me10–TFT7 complex occurs within the plant cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Tir and CagA are required for the binding of host adaptor proteins for bacterial adhesion (Nougayrede et al, 2003; Higashi et al, 2004). The plant pathogen effectors HopQ1, XopN, and XopE2 are phosphorylated in plants, which results in their associations with host 14-3-3 proteins and phosphorylated residues are required for effector virulence (Taylor et al, 2012; Li et al, 2013; Dubrow et al, 2018). In our study, the phosphorylation of AvrPtoB is required for the effector-mediated inhibition of NPR1/FLS2 accumulation and FLS2-BAK1 complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…The XopQ protein is highly conserved in Xanthomonads (Hajri et al, 2009, Moreira et al, 2010, Jalan et al, 2013, Potnis et al, 2011), and has been shown to require its biochemical activity for complete virulence in rice (Gupta et al, 2015). XopQ also has motifs for binding to 14-3-3 proteins (Dubrow et al, 2018, Deb et al, 2019). The 14-3-3 proteins are eukaryotic adapter proteins which play key roles in multiple cellular events in plants (Cotelle and Leonhardt, 2015, Cotelle et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown the role of the 14-3-3 proteins in modulation of PTI and ETI (Lozano-Duran and Robatzek, 2015), by the binding of host 14-3-3 proteins with the type III effectors of the pathogen (Dubrow et al, 2018). The ability of X. oryzae pv.…”
Section: Introductionmentioning
confidence: 99%